Toughness Calculation of Postfire Normal Concrete - Qingyang Chen; Anjing Tang; Zhoudao Lu (Advances in Materials Science and Engineering)
Fracture tests of postfire normal concrete with ten temperatures up to 600°C are implemented. Residual fracture toughness using analytical method is determined. Two situations are divided at critical load when calculating the cohesive fracture toughness. The initial and critical fracture toughness could be calculated from the complete load-crack opening displacement curves. Finally, the validation of double-K fracture model to the postfire concrete specimens is proved.